Pengaruh Kepemimpinan, Motivasi Kerja, Kepuasan Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Pt Klasse Mitra Internasional - Syah, Andrian; Siahaan , Leonard (PT. Publikasiku Academic Solution, 2025)
This study aims to analyze the influence of leadership, work motivation, job satisfaction, and work environment on employee performance at PT Klasse Mitra Internasional. Using a quantitative method and survey approach, data were collected from 60 permanent employees through a census technique. The questionnaire used was tested for validity and reliability, with Cronbach’s Alpha values ranging from 0.831 to 0.948. Descriptive statistics showed that all variables were perceived in the